The Influence of Transformational Leadership and Work Motivation on Job Satisfaction, with Contingent Reward as a Moderating Variable - Awibowo, Yogo; Ramli, Abdul Haeba (Malikussaleh University, Aceh, Indonesia, 2025)
This research analyzes the influence of transformational leadership and work motivation on job satisfaction, with contingent reward as a moderating variable. Transformational leadership and work motivation influence job satisfaction, while contingent rewards act as awards based on performance achievements. This research uses a quantitative approach with the Structural Equation Model Partial Least Squares (SEM-PLS) method. Data was collected by distributing questionnaires using Google Forms involving 100 respondents. The population in this research study was PT Tembaga Mulia Semanan Tbk; the sampling technique used was purposive sampling, namely permanent employees of PT Tembaga Mulia Semanan Tbk. The sample for this research was permanent employees of PT Tembaga Mulia Semanan Tbk. The findings of this research show that transformational leadership and work motivation influence job satisfaction. In addition, contingent rewards were not proven to moderate the relationship between transformational leadership and job satisfaction. In contrast, contingent rewards were proven to moderate the relationship between work motivation and job satisfaction. This research provides implications for companies developing a transformational leadership style and creating a reward system to increase team member motivation and job satisfaction.